Autologous Serum Skin Test versus Autologous Plasma Skin Test in Patients with Chronic Spontaneous Urticaria - Aysegul Alpay; Nilgün Solak Tekin; Ishak Özel Tekin; H. Cevdet Altinyazar; Rafet Koca; Saniye Çınar (Dermatology Research and Practice)
Previous studies indicate that 25–45% of chronic urticaria patients have an autoimmune etiology. Autologous serum skin test (ASST) and autologous plasma skin test (APST) are simple tests for diagnosing chronic autoimmune urticaria (CAU). However, there are still some questions about the specificity of these tests. This study consisted of 50 patients with chronic spontaneous urticaria (CSU) and 50 sex- and age-matched healthy individuals aged 18 years, and older. A total of 31 (62%) patients and 5 (10%) control patients had positive ASST; 21 (42%) patients and 3 (6%) control patients had positive APST. Statistically significant differences were noted in ASST and APST positivity between the patient and control groups (ASST P<0.001; APST P<0.001). Thirteen (26%) patients and 5 (10%) control patients had antithyroglobulin antibodies or antithyroid peroxidase antibody positivity. No statistically significant differences were noted in thyroid autoantibodies between the patient and control groups (anti-TG P=0.317; anti-TPO P=0.269). We consider that the ASST and APST can both be used as in vivo tests for the assessment of autoimmunity in the etiology of CSU and that thyroid autoantibodies should be checked even when thyroid function tests reveal normal results in patients with CSU.